Anthropometric and Somatotype Characteristics of Young Soccer Players: Differences Among Categories, Subcategories, and Playing Position. Issue 8 (August 2015) - Perroni, Fabrizio; Vetrano, Mario; Camolese, Giancarlo; Guidetti, Laura; Baldari, Carlo
Abstract : Abstract: Perroni, F, Vetrano, M, Camolese, G, Guidetti, L, and Baldari, C. Anthropometric and somatotype characteristics of young soccer players: Differences among categories, subcategories, and playing position. J Strength Cond Res 29(8): 2097–2104, 2015—Considering that anthropometric parameters are important factors in the performance of the soccer players, the aim of this study was to explore the differences in anthropometric and somatotype characteristics of Italian young soccer players. Weight, height, body mass index, and somatotype of 112 young soccer players, grouped in Giovanissimi "A" (14 years), "B" (13 years), and "C" (12 years) as well as Allievi "B" (15 years) and "A" (16 years) and "Juniores" (older than 17 years), were evaluated. Statistical analysis tests were computed at p ⩽ 0.05, and an analysis of variance for each somatotype was calculated to analyze the main effects and interactions of the factors: categories, subcategories, and playing position. Bonferroni's post hoc analysis was used to identify differences among mean values. Considering all subjects, we have found significant differences in categories, subcategories, and playing position between anthropometric values and a somatotype value of 2.8-3.8-2.9. Significant differences have found among goalkeepers and the others playing position in endomorphy ( p ⩽ 0.001) and with defenders and midfielders in ectomorphy ( p < 0.01) components, whereas no differences in mesomorphy. Analyzing the interaction between subcategories and playing position factors, a significant effect was found only in the endomorphy component ( p = 0.05). The analysis of anthropometric characteristic of Italian young soccer players indicates that players have high muscularity value and low adiposity. This study showed the presence of somatotype differences for playing position within categories also in the youngest categories and subcategories, in particular, in the endomorphy component. Young soccer players should be trained with more appropriate and specific training load to avoid the increased injury risk during adolescence.